2011
DOI: 10.1521/soco.2011.29.2.166
|View full text |Cite
|
Sign up to set email alerts
|

The Boss is Paying Attention: Power Affects the Functioning of the Attentional Networks

Abstract: The aim of this paper was to explore the effects of social power on basic attentional processing. Two studies were conducted to test whether powerful individuals show a greater capacity for using orienting cues to increase their executive control. In Experiment 1, participants were assigned to a powerful or a powerless role and then performed a task designed to measure three different dimensions of attentional functioning and the interactions between them: executive control, orienting, and alertness. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 44 publications
2
14
0
1
Order By: Relevance
“…Confronted with increased demands, powerless individuals are less capable of effective self-regulation, and their judgments and behaviors are guided less by the primary task at hand. These claims are supported by research using basic attentional tasks that require focused attention to a target, and inhibition of irrelevant information (Guinote, 2007b;Smith, Jostmann, Galinsky, & van Dijk, 2008;Willis, Rodríguez-Bailón, & Lupiáñez, 2011).…”
Section: Perspectives On Power and Self-regulationmentioning
confidence: 96%
See 1 more Smart Citation
“…Confronted with increased demands, powerless individuals are less capable of effective self-regulation, and their judgments and behaviors are guided less by the primary task at hand. These claims are supported by research using basic attentional tasks that require focused attention to a target, and inhibition of irrelevant information (Guinote, 2007b;Smith, Jostmann, Galinsky, & van Dijk, 2008;Willis, Rodríguez-Bailón, & Lupiáñez, 2011).…”
Section: Perspectives On Power and Self-regulationmentioning
confidence: 96%
“…(2010) found that illegitimately powerless individuals persist longer in the face of adversity, as compared to both legitimately powerless and control group participants. Second, illegitimately powerless individuals exhibited the same attentional control as the legitimately powerful do (Willis et al., 2011).…”
mentioning
confidence: 99%
“…Power sparks optimism and confidence ), authentic self-expression (Anderson & Berdahl 2002, Guinote et al 2002, action (Galinsky et al 2003), and disinhibited behavior (Gonzaga et al 2008) while decreasing vigilance (Willis et al 2011) and worries about threats or losses (Inesi 2010, Keltner et al 2003. Power holders and dominant people often experience positive affective states, such as happiness and interest (Anderson & Berdahl 2002, Berdahl & Martorana 2006, Langner & Keltner 2008, Schmid Mast et al 2009).…”
Section: Power Triggers a Generalized Approachmentioning
confidence: 99%
“…self-regulation) processes (Derryberry, 2002;Posner, 2012;Posner, Rothbart, Sheese, & Tang, 2007). 1 Third, it has been shown that personal experiences related to a sense of powerlessness (understood as lack of control in a social context) impair executive functions such as updating and inhibition (Smith, Jostman, Galinsky, & van Dijk, 2008), decrease the ability to avoid distractors and focus on goalrelevant information (Guinote, 2007), and reduce the efficiency of using spatial orienting cues to improve executive control (Willis, Rodríguez-Bailón, & Lupiáñez, 2011). These results could therefore lead to analogous predictions of detrimental effects of control deprivation on executive attention.…”
Section: Introductionmentioning
confidence: 99%